Efficiency in the MENA banking industry, the stochastic frontier approach (SFA) - Samar Rizk (Financial Markets, Institutions and Risks)
The main focus of this paper is the study of efficiency in the Middle Eastern and North African (MENA) banking industries throughout the period 1999-2017. The study of efficiency in many other regions reveals the existence of failures in the allocation of resources for banking sectors which results in the appearance of banking inefficiency in terms of cost. The empirical results, using a parametric cost frontier applied, show a fluctuating yet improving efficiency in the MENA and are used to rank efficiency of banking industries by country over the years (1999- 2017). Promoting a strong and stable banking system reduces uncertainties and systemic risk which leads to greater efficiency. A stable and efficient banking system is then, necessary, for economic development. Since 1990s, and due to reforms required by supervisory authorities, banks in the MENA region have faced many structural changes and have tried to develop their activities by seeking to enter new markets and new sectors of activity in order to adapt to the economic and institutional environment changes by adopting internal and / or external growth strategies. These strategies can increase banks market power and diversify banking industries’ activities in order to achieve efficiency gains.